2016
DOI: 10.3390/w8060229
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Weather Events and Climate Variability Provide a Lens to How Shallow Lakes May Respond to Climate Change

Abstract: Shallow lakes, particularly those in low-lying areas of the subtropics, are highly vulnerable to changes in climate associated with global warming. Many of these lakes are in tropical cyclone strike zones and they experience high inter-seasonal and inter-annual variation in rainfall and runoff. Both of those factors strongly modulate sediment-water column interactions, which play a critical role in shallow lake nutrient cycling, water column irradiance characteristics and cyanobacterial harmful algal bloom (Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 47 publications
3
59
1
2
Order By: Relevance
“…Both factors strongly modulate sediment-water column interactions, which play a critical role for shallow lake nutrient cycling, water column irradiance characteristics, and cyanobacterial harmful algal bloom dynamics. Long-term (15 to 25 years) datasets on water quality and plankton were analyzed from three shallow lakes: Lakes Okeechobee and George (Florida, USA) and Lake Taihu (China) [25]. Okeechobee and Taihu have been impacted repeatedly by tropical cyclones, creating large amounts of runoff and sediment resuspension and consequent increases in dissolved nutrients in the water column.…”
Section: Mediterranean and Subtropical Climate Zonementioning
confidence: 99%
See 1 more Smart Citation
“…Both factors strongly modulate sediment-water column interactions, which play a critical role for shallow lake nutrient cycling, water column irradiance characteristics, and cyanobacterial harmful algal bloom dynamics. Long-term (15 to 25 years) datasets on water quality and plankton were analyzed from three shallow lakes: Lakes Okeechobee and George (Florida, USA) and Lake Taihu (China) [25]. Okeechobee and Taihu have been impacted repeatedly by tropical cyclones, creating large amounts of runoff and sediment resuspension and consequent increases in dissolved nutrients in the water column.…”
Section: Mediterranean and Subtropical Climate Zonementioning
confidence: 99%
“…In Lake George, periods of high rainfall resulted in high dissolved color, reduced irradiance, and increased water turnover rates, suppressing the blooms, whereas in dry periods with lower water color and water turnover rates, there were dense cyanobacteria blooms. Using an expert judgement approach, a suite of factors were identified that will determine how a particular shallow lake will respond to a future with global warming, flashier rainfall, prolonged droughts, and stronger tropical cyclones [25].…”
Section: Mediterranean and Subtropical Climate Zonementioning
confidence: 99%
“…A proliferation of Cyanobacteria has been recorded in lacustrine phytoplanktonic communities, and studies have highlighted the possible role of climate change in promoting toxic blooms, although considerably different responses to temperature increase have been recorded among various Cyanobacteria species and among genetic strains [8,9,12,[55][56][57][58][59][60]. Moreover, these changes in lake ecosystems can lead to the introduction of allochthonous populations of Cyanobacteria, with different and not-always-identified toxicological features [4,55].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, X is the mean value of the X i during the period 1961-1990. The anomaly percentage P value of each year from 1961 to 2007 was calculated using Equation (1). Subsequently, these P values were sorted in descending order and divided into five groups at equal intervals.…”
Section: Definition Of Runoff Precipitation and Temperature Indicesmentioning
confidence: 99%
“…Global climate warming and its consequences have been discussed for years in the scientific literature and mass media, and have become the focus of attention of the scientific community [1,2]. The Intergovernmental Panel on Climate Change (IPCC) has concluded that global climate warming is mainly characterized by significant air temperature increases [3].…”
Section: Introductionmentioning
confidence: 99%